Training Scientific Literacy Skills Through Inquiry Learning with Chemcollective's Virtual Laboratory on Chemical Equilibrium - Ahmad, Muhammad Syahru; Rahayu, Yuni Sri; Sukarmin, Sukarmin (JPPS (Jurnal Penelitian Pendidikan Sains), 2023)
Objective: This study uses ChemCollective's virtual laboratory to apply inquiry learning and seeks to describe the application of inquiry learning models, student activities, scientific literacy skills, and student responses. Method: This study uses a one-group pretest-posttest pre-experimental approach. The study tools included student response questionnaires, student activity observation sheets, learning implementation observation sheets, and literacy test instruments. Results: The study's findings were as follows: (1) the inquiry learning model was implemented at 83% of the first meeting and 93% of the second meeting; (2) the average percentage of student activity that is relevant to inquiry learning was 90.24% at the first meeting and 93.60% at the second meeting; (3) the results of the scientific literacy test improved, with an N-Gain Score of 0.76 in the high category and the results of the paired sample t-test revealed a significance value of 0.000; and (4) With very favorable criteria, 98% of students respond on average to inquiry learning when using the ChemCollective virtual laboratory. These findings suggest that, during the odd semesters of the 2022–2023 academic year, first-semester Science Education Study Program students at UIN Sunan Ampel Surabaya can train their scientific literacy through inquiry learning supported by ChemCollective's virtual laboratory.